Implementação e avaliação de um vídeo educativo para famílias de pessoas com colostomia - Oliveira, Daiane de (2016)
Living with cancer and colostomy generally causes a strong impact on the person who went through the procedure as well as for his or her family due to several diseases-related circumstances. Colostomy care continues after the patient is released from the hospital. In this new phase, the patient and his or her family may have various feelings such as insecurity and doubts. In this sense, it is important that the nurse develop educative actions to offer tools to manage the colostomy and make the affected people stronger. This thesis research question is as follows: What is the repercussion of nursing intervention through an educational video to the families that have a member that went through colostomy due to cancer? The main objective is to implement and to evaluate the repercussion of nursing intervention through an educational video to the families that have a member that went through colostomy due to cancer. The specific objectives are as follows: to identify previous knowledge regarding the colostomy intervention and necessary care; to identify posterior knowledge to the colostomy-related intervention and necessary care; to learn about the family s perceptions regarding the video used in the nursing intervention; and to evaluate the repercussion of the nursing intervention through the educational video. The methodology is classified under a exploratory and descriptive approach regarding its objectives, transversal regarding data collections, and qualitative in relation to data treatment. Two hospitals were included as the research scenario, University Hospital of Santa Maria and Ijuí Charity Hospital, in Brazil. Ten families of patients with colorectal colostomy took part of the study, in a total of 24 people. Data collection took place in two distinct phases. The first phase was the implementation and nursing intervention. The second phase was the evaluation of such intervention. We utilized semi-structured interviews, and the study was conducted between May and August of 2015. Data analysis and interpretation was guided by the operative proposal of Minayo. The study follow the ethics recommendation, according to the Brazilian National Health Commission s resolution number 466/12. This current research was approved by the Ethics on Research Committee of the Federal University if Santa Maria under the following registration CAAE 28062514.8.0000.5346. This study s results were identified in four categories as follows: Colostomy- previous knowledge and intervention; I learned from the video - knowledge acquired after the nursing intervention; a normal life is possible - repercussion from watching the educational video; yes, the video is valid : perceptions of families regarding the educational video. The implementation of the nursing intervention through an educational video had a positive repercussion on the families of colorectal colostomy patients, the research participants reported that the video helped them understand the colostomy care, emotional issues and communication within the family.